Peningkatan Kualitas Produk Kripik Pare di Desa Poncosari Kepanewon Srandakan, Bantul Melalui Program Re-branding - Imam Suprabowo; Wulan Noviani; Cahyo Setiadi Ramadhan (Universitas Muhammadiyah Surakarta, 2022)
The COVID-19 pandemic has had a broad impact on the economic sector, including the people of Koripan, Poncosari, Srandakan. Facing these conditions, the community took the initiative to try to produce and sell snack products made from bitter melon vegetables. The high yield of bitter gourd and the low selling price of bitter gourd have the potential to generate sufficient income for the community. This potential can be further increased by improving product quality, packaging, and marketing. In addition, the opportunity for these products needs to be maintained by registering the product with the authorities and minimizing the chances of product imitation. To fulfill these potentials, the service team collaborates with the community producing the bitter gourd snack products as partners to carry out several activities. Servants and partners improve the quality of snack products by adding product variants that can also increase the nutritional levels or benefits of these snacks for consumer nutrition. Servants together with partners improve the quality of product packaging designs so that they are more adequate to be sold at favorable prices. The servant registers the innovations carried out, namely the improvement of the product design to the authorized institution to prevent product imitations in the future. Based on interviews with partners, it is known that partners feel the benefits of the program, namely adding product flavor variants, improving packaging quality, and protecting their products. In addition, there was an increase in orders for partner products after the implementation of the service program. Before the service, an average of 15 packs were sold per month. But after the service there was an increase to 113 packs.